(Working) memory and L2 acquisition and processing. (July 2017) - Rankin, Tom
This review evaluates two recent anthologies that survey research at the intersection of cognitive psychological investigations of (working) memory and issues in second language (L2), and bilingual processing and acquisition. The volumes cover similar ground by outlining the theoretical underpinnings of models of (working) memory as well as providing empirical tests of a range of topics in bilingual and L2 acquisition and use. However, while one volume focuses specifically on issues of working memory and L2 acquisition and processing, the other provides a broader overview of the interface between memory and bilingualism more generally. Taken together, the volumes present a large array of research and will be a valuable resource for students and researchers interested in issues in bilingual memory, processing and acquisition.